Design of valveless micropump using preliminary characteristics from fluid flow - D., Ramasamy; Mahendran, Samykano; Z. A. A., Karim; Nagarajan, T. (Asian Network for Scientific Information, 2011)
The need for cooling in advance thermal systems is ever in demand. The administration of such cooling will need miniaturization of the current pumping system for small-scale use. A valve less pump is one of the methods to create a small microscale flowrate pump. It has intake and outlet on the same side. Advances in fluid mechanics are able to capture the working principles of such pumps and give a close approximation of the pump characteristics. The fundamental aspect that a micropump will endure is analyzed from fluid mechanics analysis, is a key in the development of the model. The sizing and criteria of the pump is set based on fluid equations of mass, momentum and energy. A design is laid out by using computer-aided design (CAD) based on the voltage frequency that will be applied to the piezomaterial. The movement of the material due to current will cause the fluid to move, as the material will act as a diaphragm. The design is then analyzed using computational fluid dynamics (CFD) from the frequency inputs and a steady flow design is simulated. The reading of the small flowrate is analyzed and a proper method of designing the valve less pump is gathered.